Centrifuge experiment on the penetration test for evaluating undrained strength of deep-sea surface soils - Guo, Xingsen; Nian, Tingkai; Zhao, Wei; Gu, Zhongde; Liu, Chunpeng; Liu, Xiaolei; Jia, Yonggang (International journal of mining science and technology, 2022)
Rapid advances in deep-sea mining engineering have created an urgent need for the accurate evaluation of the undrained strength of marine soils, especially surface soils. Significant achievements have been made using full-flow penetration penetrometers to evaluate marine soil strength in the deep penetration; however, a method considering the effect of ambient water on the surface penetration needs to be established urgently. In this study, penetrometers with multiple probes were developed and used to conduct centrifuge experiments on South China Sea soil and kaolin clay. First, the forces on the probes throughout the penetration process were systematically analyzed and quantified. Second, the spatial influence zone was determined by capturing the resistance changes and sample crack development, and the penetration depth for a sample to reach a stable failure mode was given. Third, the vane shear strength was used to invert the penetration resistance factor of the ball and determine the range of the penetration resistance factor values. Furthermore, a methodology to determine the penetration resistance factors for surface marine soils was established. Finally, the effect of the water cavity above various probes in the surface penetration was used to formulate an internal mechanism for variations in the penetration resistance factor.